Liver exposure during laparoscopic right-sided hepatectomy via stretching of the ligamentum teres hepatis: A propensity score matching analysis - Song, Keda; Xu, Yang; Li, Zhongyu; Wang, Mingyuan; Chen, Dong; Zhou, Yongzhi; Yang, Guangchao; Ma, Yong (BioScience Trends, 2025)
One of the challenges of laparoscopic liver resection (LLR) is the exposure of the surgical field. We propose a new surgical approach to better expose the right liver, stretching of the ligamentum teres hepatis (SLTH), and we evaluated its clinical feasibility and limitations through a study analyzing relevant cases. Clinicopathologic data on patients who underwent laparoscopic right partial hepatectomy (LRPH) at our center were retrospectively collected, and subjects were 276 patients with liver space-occupying lesions who met the selection criteria and who underwent the new surgical approach (SLTH) or the conventional surgical approach (no stretching of the ligamentum teres hepatis, or NSLTH). After 1:1 propensity score matching (PSM), 102 patients in each cohort were selected for further analysis. There were no significant differences in the operating time or the duration of postoperative hospitalization between the SLTH cohort and the NSLTH cohort. The duration of detachment of the hepatic parenchyma and the duration of hepatic portal occlusion were significantly shorter in the SLTH cohort than in the NSLTH cohort. The intraoperative blood loss in the SLTH cohort was significantly less than that in the NSLTH cohort. Alanine aminotransferase (ALT) and aspartate aminotransferase (AST) levels were significantly lower in the SLTH cohort than in the NSLTH cohort on day 5 postoperatively. Results confirmed that SLTH is a simple, safe, effective, and highly reproducible technique for the treatment of LRPH. SLTH may help to perform LRPH by increasing the level of laparoscopic exposure of the right liver and reducing bleeding and operating time.